Community Structure and Biodiversity of Insects in Rice Paddy Field at Different Varieties - แซ่ตั้ง, วีรนุช; บุญชู, นุชนาฎ; พูลประเสริฐ, พิสิษฐ์ (YRU Journal of Science and Technology, 2018)
The purpose of this current research was to determine the community structure together with biodiversity of insects that use rice paddy fields at various rice varieties. Three main varieties of rice i.e. RD 41, Pathum Thani 80 and Phitsanulok 2 in tiller stage from Thab Man sub-district, Taphan Hin district, Phichit province were selected. Three sampling plots of paddy field in each rice variety were chosen and insects were caught using sweeping net at 20 times/sampling plot during June to July 2017. All samples were identified based on external morphology. Fifty-Three insect species, 37 families obtained were representative of 11 orders. RD 41 showed the highest diversity (40 species). Herein, species diversity (H’) for all insect of all rice varieties was considered relatively high. However, the highest insect species diversity index (H’), Evenness (J’) and Simpson index (D) in RD 41 obtained from the pooled data set of this survey were 2.89, 0.82 and 0.91, respectively. Based on similarity index (Ss), the assemblage recorded of rice insect among various rice varieties shared ranging from 0.66-0.74. Additionally, the insect pests namely, Hydrellia philippin (F. Ephydridae), Prodiplosis longifila (F. Cecidomyiidae) and Edwardsiama hergmanni (F. Cicadellidae) were the dominant species. Whereas, Micraspis discolor (F. Coccinellidae), Agriocnemis pygmaea (F. Agrionidae) and Ommatius sp. (Asillidae) were mainly exhibited in this time.